Sand flies (Diptera: Psychodidae) in eight Balkan countries: historical review and region-wide entomological survey - Dvorak, Vit; Kasap, Ozge Erisoz; Ivovic, Vladimir; Mikov, Ognyan; Stefanovska, Jovana; Martinkovic, Franjo; Omeragic, Jasmin; Pajovic, Igor; Baymak, Devrim; Oguz, Gizem; Hlavackova, Kristyna; Gresova, Marketa; et al. (Parasites & vectors, 2020)
BACKGROUND: Sand flies (Diptera: Psychodidae) are medically important vectors of human and veterinary disease-causing agents. Among these, the genus Leishmania (Kinetoplastida: Trypanosomatidae), and phleboviruses are of utmost importance. Despite such significance, updated information about sand fly fauna is missing for Balkan countries where both sand flies and autochtonous leishmaniases are historically present and recently re-emerging. Therefore, a review of historical data on sand fly species composition and distribution in the region was followed by a large-scale entomological survey in eight Balkan countries to provide a recent update on local sand fly fauna. METHODS: The literature search involved the period 1910-2019. The entomological survey was conducted at 1189 sampling stations in eight countries (Bulgaria, Bosnia and Herzegovina, Croatia, Kosovo, Montenegro, North Macedonia, Serbia and Slovenia), covering 49 settlements and 358 sampling sites between June and October in the years 2014 and 2016, accumulating 130 sampling days. We performed a total of 1189 trapping nights at these stations using two types of traps (light and CO2 attraction traps) in each location. Sampling was performed with a minimal duration of 6 (Montenegro) and a maximal of 47 days (Serbia) between 0-1000 m.a.s.l. Collected sand flies were morphologically identified. RESULTS: In total, 8490 sand fly specimens were collected. Morphological identification showed presence of 14 species belonging to genera Phlebotomus and Sergentomyia. Historical data were critically reviewed and updated with our recent findings. Six species were identified in Bosnia and Herzegovina (2 new records), 5 in Montenegro (2 new records), 5 in Croatia (2 new records), 9 in Bulgaria (5 new records), 11 in North Macedonia (1 new record), 10 in Serbia (no new records), 9 in Kosovo (3 new records) and 4 in Slovenia (no new records). CONCLUSIONS: This study presents results of the first integrated sand fly fauna survey of such scale for the Balkan region, providing first data on sand fly populations for four countries in the study area and presenting new species records for six countries and updated species lists for all surveyed countries. Our findings demonstrate presence of proven and suspected vectors of several Leishmania species.
Keywords: Psychodidae; Animal Distribution; Male; Phlebotomine; Sand fly; Balkan Peninsula; Leishmaniasis; Balkans; mužské pohlaví; hmyz - vektory; rozšíření zvířat; Balkánský poloostrov; Species; Morphology; Animals; ženské pohlaví; zvířata; Insect Vectors; leishmanióza; Female